طريقة تحليلية جديدة لتعيين Ti(IV) في العينات الصخرية والرملية (مجلة جامعة اللاذقية - سلسلة العلوم الأساسية, 2018)
A simple, selective and sensitive spectrophotometric method has been proposed for the determination of Ti(IV) using a newly  synthesized 3- acetylpentane-2,4-dione (ACPD). The effect  of pH, time of reaction and temperature were estimated. The stoichiometry of the complex was found to be 1:10 (metal:ligand).The effect of foreign ions in the determination of Ti(IV)) was investigated. Beer's law is obeyed for titanium concentration in the range (5 - 95µg/25 ml)at 400 nm.The molar absorptivity and Sandell’s sensitivity of the coloured complex are 1.5 x104 L mol−1 cm−1, and 3.20x10-3μg. cm-2 respectively. The RSDs  was below 3.5%. The proposed method has been successfully applied to determine of titanium in natural and standard  samples. تعرض هذه الورقة البحثية طريقة تحليلية جديدة لتعيين التيتانيوم طيفياً باستخدام كاشف تحليلي جديد هو " 3- أسيتيل بنتان -2،4 – ديون الذي يتفاعل مع Ti(IV) ويشكل معقداً بامتصاصية أعظمية عند الطول الموجي λmax= 400 nm. تتصف هذه الطريقة بالبساطة والانتقائية والحساسية العالية وسرعة التنفيذ . درس تأثير حموضة الوسط و كمية الكاشف التحليلي و زمن التفاعل ودرجة الحرارة ووجود أيونات التداخل في تعيين التيتانيوم وعيّنت الشروط المثلى للتعيين. وجد أن امتصاصية المعقد تخضع لقانون بيير في مجال واسع من تركيز  Ti(IV)          (5 -  95µg/25 ml) . كما وجد أن معامل الامتصاص المولي لهذا الكاشف يساوي 1.5 x104 L.mol-1cm-1 وأن حد الكشف يساوي   0.01µg/ ml ومعامل  ساندل  يساوي  3.20 x 10 -3μg .cm-2 وأن الانحراف المعياري النسبي لايتجاوز 3.5%. طبقت هذه الطريقة في تعيين Ti(IV) في بعض العينات المعيارية والطبيعية.